Better fiscal rules for Europe: Reflections based on new empirical evidence - Zareh Asatryan; Dirk Foremny; Friedrich Heinemann; Albert Solé-Ollé; Thomas Stratmann; Mustafa Yeter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Over the past five years, the euro area's fiscal rules have been reformed and extended. It is not clear, however, whether these changes have been effective at boosting fiscal prudence, and whether they go far enough. This policy paper summarises recent research findings from a Spanish-German-American team led by ZEW. The study considers the general effectiveness of fiscal rules in the past and the interactions between rules, political factors and fiscal equalization. One key recommendation is that fiscal governance should pay more attention to budgetary developments in the seemingly good times, explicitly addressing the use of windfall revenues and the build-up of large bureaucracies.
Keywords: 330